1997
DOI: 10.1136/bmj.315.7116.1126
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the NHS reforms on English hospital productivity: an analysis of the first three years

Abstract: Further analysis is needed to determine whether overall and trust associated productivity gains are transient effects, one off shifts, or self perpetuating reorientations of organisational behaviour. Hospitals may have chosen to become trusts because they anticipated being able to increase productivity. Increases in the proportions of small purchasers were associated with increasing costs. Importantly, this study could not adjust for changes in the quality of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 14 publications
1
22
0
Order By: Relevance
“…Hospitals with few competitors, on the other hand, had lower costs on average in 1991/2, but made little by way of cost savings during the study period. Similar effects to those of Sö derlund et al [24] were found with regard to purchaser monopsony power. Lastly, Csaba found a significant interaction effect between trust status and market concentration: trusts were more responsive to competition than directly managed units, other factors being equal.…”
Section: The Effect Of Competition On Costssupporting
confidence: 85%
See 2 more Smart Citations
“…Hospitals with few competitors, on the other hand, had lower costs on average in 1991/2, but made little by way of cost savings during the study period. Similar effects to those of Sö derlund et al [24] were found with regard to purchaser monopsony power. Lastly, Csaba found a significant interaction effect between trust status and market concentration: trusts were more responsive to competition than directly managed units, other factors being equal.…”
Section: The Effect Of Competition On Costssupporting
confidence: 85%
“…But to our knowledge, only one published study and one piece of as yet unpublished work, have examined the impact of competition between providers on costs. Sö derlund et al [24] examined the effect of competition on average costs per inpatient episode (including capital charges) for acute care hospitals in England for the years 1991/2-1993/4. Adjustments were made for levels of non-inpatient care, case mix, long stay out episodes, teaching, and trust status, hospital size level of specialisation, and mix of purchasers.…”
Section: The Effect Of Competition On Costsmentioning
confidence: 99%
See 1 more Smart Citation
“…Information on quality was very limited. The evidence suggests that greater competition was associated with lower costs (Söderlund et al, 1997). The bargaining power of district health authorities was lower than that of GP fundholders, and hospitals that had greater business from fundholders had lower posted prices (Propper et al, 1998;Propper, 1996).…”
Section: Evidence From the Ukmentioning
confidence: 99%
“…Among these studies, So¨derlund et al (1997) estimated a classical linear regression model on a sample of NHS hospitals in England for the years 1992 to 1994, which revealed a general productivity improvement, however not associated to trust status. Due to its easier availability, others have used the acute Scottish hospitals data set used in this paper.…”
Section: Introductionmentioning
confidence: 99%